2012
DOI: 10.1186/1471-2407-12-319
|View full text |Cite
|
Sign up to set email alerts
|

AB0 blood group and prognosis in patients with pancreatic cancer

Abstract: Background Although blood group 0 is associated with a reduced risk of pancreatic cancer, little is known about the role of AB0 blood group antigens in disease progression. We assessed the prognostic relevance of AB0 blood status in a large cohort of patients with resected pancreatic cancer. Methods A total of 627 patients, who underwent resection for pancreatic ductal adenocarcinoma between October 2001 and December 2008 were enrolled. The relationship between AB0 bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
50
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 44 publications
12
50
1
Order By: Relevance
“…Blood group AB did not show a change in frequency, but this is probably due to the small sample size of patients with PDAC. In general, our findings are in accordance to previous studies, which as well showed a lower frequency of PDAC in blood group O (3,27,28).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Blood group AB did not show a change in frequency, but this is probably due to the small sample size of patients with PDAC. In general, our findings are in accordance to previous studies, which as well showed a lower frequency of PDAC in blood group O (3,27,28).…”
Section: Discussionsupporting
confidence: 93%
“…These findings are also in consistence with a previous study, which failed to show significant differences in clinicopathologic characteristics among patients with different ABO blood groups (28). In contrast, tumor grading (G) showed significant differences within Figure 3.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To date, this has been examined only in studies with a smaller sample size than ours (16,17) with inconsistent results. The samples from Germany partially overlap with those used in a recent study (28). Due to the lack of information on CA19-9, lymph node status and grading, we were not able to replicate the statistically significant (0.037) association they found using a multivariate analysis.…”
Section: Discussionmentioning
confidence: 68%
“…including colon cancer, pancreatic cancer, nasopharyngeal carcinoma, esophageal cancer, breast cancer, skin cancer, renal cell carcinoma and gastric cancer [7][8][9][10][11][12][13][14]. Although the study by Lee et al established the survival of NSCLC patients who received curative surgery within the context of ABO blood group, the aim of their study was to investigate the prognostic role of expression of blood group antigen A in tumor cells [15].…”
Section: Introductionmentioning
confidence: 99%